Age and pupil size: key predictors of mortality in traumatic brain injury patients with GCS 3 - Eric Nyam, Tee-Tau; Tu, Kuan-Chi; Kuo, Yun-Hsuan; Wang, Che-Chuan; Liu, Chung-Feng; Liao, Jen-Chieh; Kuo, Ching-Lung (Frontiers in Neurology, 2025)
This study investigates the relationship between mortality and specific clinical factors in patients with severe traumatic brain injury (TBI) who present with a Glasgow Coma Scale (GCS) score of 3. Data from 161 adult patients were collected from the Chi-Mei Medical Center in Taiwan, spanning 2010 to 2019. The findings revealed an overall mortality rate of 44.10%, with significant predictors of mortality identified as age and pupil size. The Spearman correlation analysis showed that both age and pupil sizes were positively correlated with mortality rates. Multiple logistic regression confirmed age and left pupil size as strong predictors of mortality. Patients with GCS 3 and both unreactive pupils measuring 4 mm or more experienced the highest mortality rate of 68.39%, while those with pupils less than 4 mm had a lower mortality rate of 32.26%. The study determined optimal cut-off values for age and pupil size using ROC and AUC analysis, highlighting the significance of age in mortality predictions. These findings underscore the critical role of age and pupil size in the prognosis of TBI patients and provide valuable guidance for clinicians managing such cases.